Helminth Infections: Recognition and Modulation of the Immune Response by Innate Immune Cells - Motran, Claudia Cristina; Silvane, Leonardo; Chiapello, Laura Silvina; Theumer, Martin Gustavo; Ambrosio, Laura Fernanda; Volpini, Ximena; Celias, Daiana Pamela; Cervi, Laura (Frontiers in Immunology, 2018)
The survival of helminths in the host over long periods of time is the result of a process of adaptation or dynamic co-evolution between the host and the parasite. However, infection with helminth parasites causes damage to the host tissues producing the release of danger signals that induce the recruitment of various cells, including innate immune cells such as macrophages, dendritic cells, eosinophils, basophils and mast cells. In this scenario, these cells are able to secrete soluble factors, which orchestrate immune effector mechanisms that depend on the different niches these parasites inhabit. Here, we focus on recent advances in the knowledge of excretory secretory products (ESP), resulting from helminth recognition by dendritic cells and macrophages. Phagocytes and other cells types such as innate lymphocyte T cells 2 (ILC2), when activated by ESP, participate in an intricate cytokine network to generate innate and adaptive Th2 responses. In this review, we also discuss the mechanisms of innate immune cell induced parasite killing and the tissue repair necessary to assure helminth survival over long periods of time.